Implementing English for Specific Purposes (ESP) in a Multi-Major Vocational Context: A Qualitative Case Study of Software Engineering and Electrical Installation Programs - Hanapiah, Jihan; Muljanto, Setia; Setiawati, Pipih (Journal of English Language and Education, 2026)
English for Specific Purposes (ESP), defined by Hutchinson and Waters (1987) as a goal oriented approach that tailors language instruction to learners’ specific professional needs, occupies a central place in vocational education in Indonesia. Current policies such as the Merdeka Curriculum and Ministerial Decree No. 244/M/2024 emphasize that English instruction in vocational high schools must prepare students for the linguistic demands of their respective fields rather than for general communication alone. However, existing studies primarily investigate ESP within a single vocational major and focus on needs analysis or material development, leaving limited understanding of how teachers implement ESP simultaneously across different departments with distinct technical discourses under one curriculum framework. This study aims to examine how ESP materials are implemented in two majors, Software Engineering (RPL) and Electrical Installation Engineering (TITL), at SMK Teknologi Mandiri in Garut, West Java. A qualitative descriptive design was employed through four classroom observations and semi structured interviews with two experienced English teachers. The findings reveal four consistent implementation strategies: technical vocabulary introduction, genre contextualization of national curriculum text types, authentic material use, and vocational task simulation. The study also identifies three major challenges, namely limited instructional time, demands on teachers’ technical knowledge, and varied student proficiency levels. The findings suggest that effective ESP implementation in a multi major vocational context depends on interdisciplinary collaboration and adaptive material development to align curriculum requirements with workplace communication needs, thereby strengthening students’ readiness for Field Work Practice.